Development of a system to analyze oral frailty associated with Alzheimer's disease using a mouse model - Kuramoto, Eriko; Kitawaki, Ayano; Yagi, Takakazu; Kono, Hiroshi; Matsumoto, Shin-Ei; Hara, Hiromitsu; Ohyagi, Yasumasa; Iwai, Haruki; Yamanaka, Atsushi; Goto, Tetsuya (Frontiers in Aging Neuroscience, 2022)
The rapid aging of the population makes the detection and prevention of frailty increasingly important. Oral frailty has been proposed as a novel frailty phenotype and defined as a decrease in oral function coexisting a decline in cognitive and physical functions. Oral frailty has received particular attention in relation to Alzheimer's disease (AD). However, the pathomechanisms of oral frailty related with AD remains unknown. It is assumed that the mesencephalic trigeminal nucleus (Vmes), which controls mastication, is affected by AD pathology, and as a result, masticatory function may be impaired. To investigate this possibility, we included male 3×Tg-AD mice and their non-transgenic counterpart (NonTg) of 3–4-months of age in the present study. Immunohistochemistry revealed amyloid-β deposition and excessive tau phosphorylation in the Vmes of 3×Tg-AD mice. Furthermore, vesicular glutamate transporter 1-immunopositive axon varicosities, which derived from Vmes neurons were significantly reduced in the trigeminal motor nucleus of 3×Tg-AD mice. To investigate whether the AD pathology observed in the Vmes affects masticatory function, we analyzed electromyography of the masseter muscle during feeding. The 3×Tg-AD mice showed a significant delay in masticatory rhythm compared to NonTg mice. Furthermore, we developed a system to simultaneously record bite force and electromyography of masseter, and devised a new method to estimate bite force during food chewing in mice. Since the muscle activity of the masseter showed a high correlation with bite force, it could be accurately estimated from the muscle activity. The estimated bite force of 3×Tg-AD mice eating sunflower seeds was predominantly smaller than that of NonTg mice. However, there was no difference in masseter weight or muscle fiber cross-sectional area between two groups, suggesting that the decreased bite force and delayed mastication rhythm observed in 3×Tg-AD mice were not due to abnormality of the masseter. In conclusion, the decreased masticatory function observed in 3×Tg-AD mice was most likely caused by AD pathology in the Vmes. Thus, novel quantitative analyses of masticatory function using mouse model of AD enabled a comprehensive understanding of oral frailty pathogenesis.